In the right place, at the right time: the integration of bacteria into the Plankton Ecology Group model - Hongjae Park; Tanja Shabarova; Michaela M. Salcher; Lenka Kosová; Pavel Rychtecký; Indranil Mukherjee; Karel Šimek; Petr Porcal; Jaromír Seďa; Petr Znachor; Vojtěch Kasalický (Microbiome, 2023)
Abstract Background Planktonic microbial communities have critical impacts on the pelagic food web and water quality status in freshwater ecosystems, yet no general model of bacterial community assembly linked to higher trophic levels and hydrodynamics has been assessed. In this study, we utilized a 2-year survey of planktonic communities from bacteria to zooplankton in three freshwater reservoirs to investigate their spatiotemporal dynamics. Results We observed site-specific occurrence and microdiversification of bacteria in lacustrine and riverine environments, as well as in deep hypolimnia. Moreover, we determined recurrent bacterial seasonal patterns driven by both biotic and abiotic conditions, which could be integrated into the well-known Plankton Ecology Group (PEG) model describing primarily the seasonalities of larger plankton groups. Importantly, bacteria with different ecological potentials showed finely coordinated successions affiliated with four seasonal phases, including the spring bloom dominated by fast-growing opportunists, the clear-water phase associated with oligotrophic ultramicrobacteria, the summer phase characterized by phytoplankton bloom-associated bacteria, and the fall/winter phase driven by decay-specialists. Conclusions Our findings elucidate the major principles driving the spatiotemporal microbial community distribution in freshwater ecosystems. We suggest an extension to the original PEG model by integrating new findings on recurrent bacterial seasonal trends. Video Abstract